STUDYING MINIATURE WORKS AND THE IMPORTANCE OF AESTHETIC EDUCATION IN IT (American Journal of Business Management, Economics and Banking, 2022)
The study of fine arts and works of applied art expands the human mind and increases its relationship with the surrounding environment. The study of miniature art opens wide opportunities for the formation of talented and talented young people. Such a person will increase feelings of beauty, goodness, love for nature and the Motherland in his heart. Increases interest in history, national traditions and glorifies it.